Multiple shoot regeneration in kokum and camboge - Madhusoodanan, S N Potty, K Mary Mathew, Y S Rao, K M Kuruvilla, R Lakshmanan, Gilu Lizy George, K J (Journal of Spices and Aromatic Crops, 2001)
Kokum (Garcinia indica Choisy) and camboge (Garcinia gummi-gutta (L.) Rob.), widely distributed in the Western Ghats remained neglected even though they are highly valued in South Indian cuisine and in traditional systems of medicine. Recently Garcinia has excited the scientific community for the indication that the fruit rind is the richest natural source of hydroxy citric acid, a potential anti obesity agent (Heymsfield et al. 1998; Muthulakshmi & Sarah 1999). The present paper deals with development of tissue culture protocols for multiplication of kokum and camboge.